Is size the only determinant of delayed abdominal closure in pediatric liver transplant?. Issue 3 (March 2017) - Khorsandi, Shirin Elizabeth; Day, Arthur William Raven; Cortes, Miriam; Deep, Akash; Dhawan, Anil; Vilca‐Melendez, Hector; Heaton, Nigel
Abstract : The aim was to determine the factors associated with the use of delayed abdominal closure in pediatric liver transplantation (LT) and whether this affected outcome. From a prospectively maintained database, transplants performed in children (≤18 years) were identified (October 2010 to March 2015). Primary abdominal closure was defined as mass closure performed at time of transplant. Delayed abdominal closure was defined as mass closure not initially performed at the same time as transplant; 230 children underwent LT. Of these, 176 (76.5%) had primary closure. Age was similar between the primary and delayed groups (5.0 ± 4.9 versus 3.9 ± 5.0 years; P = 0.13). There was no difference in the graft‐to‐recipient weight ratio (GRWR) in the primary and delayed groups (3.4 ± 2.8 versus 4.1 ± 2.1; P = 0.12). Children with acute liver failure (ALF) were more likely to experience delayed closure then those with chronic liver disease (CLD; P < 0.001). GRWR was similar between the ALF and CLD (3.4 ± 2.4 versus 3.6 ± 2.7; P = 0.68). Primary closure children had a shorter hospital stay ( P < 0.001), spent fewer days in pediatric intensive care unit (PICU; P = 0.001), and required a shorter duration of ventilation ( P < 0.001). Vascular complications (arterial and venous) were similar (primary 8.2% versus delayed 5.6%; P = 0.52). Graft ( P = 0.42) and child survival ( P = 0.65) in the primary and delayed groups were similar. Considering timing of mass closure after transplant, patients in the early delayed closure group (<6 weeks) were found to experience a shorter time of ventilation ( P = 0.03) and in PICU ( P = 0.003). In conclusion, ALF was the main determinant of delayed abdominal closure rather than GRWR. The optimal time for delayed closure is within 6 weeks. The use of delayed abdominal closure does not adversely affect graft/child survival. Liver Transplantation 23 352–360 2017 AASLD .